PENGARUH KUALITAS PRODUK, PROMOSI, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK RINSO DI RT 07 PACARKEMBANG, SURABAYA - HARDIYANA, NOVITA (Jurnal Pendidikan Tata Niaga (JPTN), 2016)
Quality Rinso always innovate the products according to the needs and desires of consumers. The quality of products that have more selling points in accordance with the wishes and needs of consumers. The study population was a resident of RT 07 Pacarkembang, Surabaya amount of125. These samples obtained from slovin formula with 10% error, so included 95 respondents respondents was randomly assigned and proportional to the area sampled random sampling technique. Based on the results analaisis in this study stated that the quality of products, promotions, prices and positive effect on product purchasing decisions Rinso. Keywords: Product Quality, Promotion, Price, and Purchase Decision